Preleukemic phase of chronic myelogenous leukemia: A diagnostic dilemma highlighting the significance of integrated reporting - Neelum Mansoor; Naila Rafiq; Sidra Maqsood; Naeem Jabbar (Pediatric Hematology Oncology Journal, 2023)
Background: A few cases pose a challenge and require data interpretation of all the tests together to establish a diagnosis. The process of independently conveying results of different diagnostic modalities by varied sections of a laboratory may lead to a delay in diagnosis. The multidisciplinary approach necessitates integrated reporting to be a part of clinical laboratories. Case report: We report a challenging case of a 7-year-old female who underwent multiple bone marrow biopsies and the diagnosis remained inconclusive. The initial blood counts revealed leukopenia, thrombocytosis and 3% population of mononuclear cells positive for CD34 by flowcytometry. Bone marrow biopsy raised suspicion of myelofibrosis. Cytogenetic and molecular studies were decisive to establish the diagnosis of chronic myelogenous leukemia in preleukemic phase. Conclusion: Coordination and communication among different sections of hematology-oncology laboratory is valuable for establishing a diagnosis.